Comparison of the diagnostic value of liquid biopsy in leptomeningeal metastases: A systematic review and meta-analysis - Wang, Hanbin; Wang, Luxuan; Fang, Chuan; Li, Chunhui; Zhang, Lijian (Frontiers in Oncology, 2022)
Background: Brain metastases (BM) include brain parenchymal (BPM) and leptomeningeal metastases (LM), which are associated with a poor prognosis and high mortality rate. Early and accurate diagnosis and timely, effective treatment are crucial for improving the overall survival of LM patients. Cerebrospinal fluid (CSF) biopsy technology has attracted widespread attention for its diagnostic value in diverse cancers, including LM. We summarized studies to compare the potential diagnostic value of CSF liquid biopsy techniques in BM patients with meta-analysis. Methods: We obtained the literature on liquid biopsy for BM from 7 databases (PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, and Wanfang Data knowledge service platform). Then, a systematic review of those studies was performed according to PRISMA criteria. Results: Nine publications have been obtained, and we found CSF liquid biopsy techniques to be more suitable for diagnosing LM. We analyzed the sensitivity, specificity, and area under the curve (AUC) of CSF liquid biopsy. The overall sensitivity, specificity, and AUC of CSF liquid biopsy in the diagnosis of LM were 0.65 (95% CI: 0.48 - 0.79), 0.70 (95% CI: 0.50 - 0.86), and 0.69, respectively. Then, we compared the diagnostic advantages of CSF liquid biopsy techniques and CSF cytology in LM. The results show that CSF liquid biopsy is superior to CSF cytology in LM diagnosis. Conclusions: Our meta-analysis suggested that CSF liquid biopsy is more suitable for LM diagnosis and has higher accuracy than CSF cytology.